Application of Jatropha Rind Compost as K Source in The Sweet Corn (Zea mays saccharata Sturt.) Cultivation - Arrasyid, Bagus; Budiyanto, Gunawan; Widyastuti, Titiek (Universitas Muhammadiyah Yogyakarta, 2017)
Potassium is one of important soil nutrients. The content of potassium in the jatropha rind compost is quite high reaching 11.36%. The high content of potassium in the jatropha rind has potential to increase the productivity and fulfill the needs of soil nutrients in the cultivation process. The research aims to study the influence of jatropha rind compost as substitute KCl fertilizer on sweet corn (Zea mays saccharata Sturt.), and get the proper rate of the compost for increasing the growth and yield of sweet corn. This research was conducted using an experimental method with a single factor that was arranged in a completely randomized design. Treatments were combination of jatropha rind compost and KCl rate, consisting of four levels, 250 kg KCl/hectare + 0 KJP kg/hectare, 125 kg KCl/hectare + KJP 273.89 kg/hectare, 62.5 kg KCl/hectare + KJP 410.84 kg/hectare, 0 kg KCl/hectare + KJP 547.79 kg/hectare. Each treatment was replicated 3 times so that there were 12 experimental units and each unit consisting of three plants trial so that there were 36 plants. Each plot of the experimental unit was fertilized using manure 20 ton/hectare, urea 400 kg/hectare which was applied 2 times and SP-36 300 kg/hectare. Results indicate that the treatment of mix dose of compost rind jatropha and KCl does not affect significantly on growth and yield of sweet corn. Sweet corn plants fertilized with jatropha rind compost with the dose of 547.79 kg/ha had the same growth and yield those of 250 kg/ha KCl. The study concluded that jatropha rind compost can replace KCl fertilizer.